Transitions in labour market status in EU labour markets - Melanie Ward-Warmedinger; Corrado Macchiarelli (IZA Journal of European Labor Studies, 2014)
We discuss the ease with which individuals can move between employment, unemployment and inactivity over time in the EU. Transitions from unemployment and inactivity back into employment are relatively weak in Central Eastern, Mediterranean and Continental European labour markets compared to Nordic European countries. On the basis of a mobility index used in the paper (Shorrocks, Econometrica, 46:1013-1024, 1978), labour markets in Spain, Luxemburg, the Netherlands, Denmark and Sweden are the most mobile, with these results mainly reflecting mobility of people below the age of 29, highly educated and female workers. Looking at some "macro" explanatory factors, the results suggest a mixed picture.
Keywords: J21; J60; J82; E24; 330; Transition probabilities; Labour market mobility; LFS micro data; EU countries